The Important Thermal Characteristics of Matter and Their Computations with the Use of the Gibbs Potentials - Budzhak, Y. S.; Wacławski, T. (Physics and Chemistry of Solid State, 2019)
In this paper, the important thermal characteristics of matter (they describe thermodynamic systems in a state of thermodynamic equilibrium) were calculated. There are the following important thermodynamic functions: the system internal energy , the thermal function (or enthalpy) the free Helmholtz energy, the thermo-dynamic potential (or Gibbs free energy), the Gibbs grand thermodynamic potential , the entropy , the specific heat capacity . These functions are explicit functions of system’s parameters, they fulfil some mathe-matical relationships and posses some total differentials. These functions are calculated in this paper and their physical sense is given in the cited works.